Estudo do compartilhamento de antígenos entre Angiostrongylus spp. e outros helmintos - Cognato, Bianca Barbieri (2013)
Two species of parasites nematode of Angiostrongylidae family, genus Angiostrongylus intra-arterial localization are capable of human desease production: Angiostrongylus costaricensis and Angiostrongylus cantonensis. Both species are rodent s parasites and the human infection is considered incidental. On humans, A. cantonensis cause eosinophilic meningitis and A. costaricensis cause abdominal angiostrongiliase. Since there is no elimination of parasitic forms in human infection, diagnosis becomes difficult and molecular methods are necessary. After years of discovery of angiostrongilíases, there are still many efforts in the study and development of a specific and sensitive diagnostic test capable of discriminating Angiostrongyliases of the other parasites. In this context, cross-reactivity becomes a problem in specificity of serologic tests. The main objective of this study was to analyze the sharing of antigens between Angiostrongylus spp. and parasites Strongyloides spp., Fasciola hepatica, Ascaris lumbricoides, Hymenolepis diminuta and Toxocara canis, and identify these molecules shared. To obtain antigens, some rats were captures and their feces analyzed by the method of Baerman addition to being seeded Agar Plates. Were obtained larvae of Strongyloides spp. and Angiostrongylus spp. In pulmonary arteries were found 11 female worms and 2 male worms of A. cantonensis, which led to the first report of the occurrence of this parasite in Rio Grande do Sul. In the small intestine was obtained a Strongyloides spp worm and analysis of small intestine were obtained Hymenolepis diminuta worms. From the adult worms of parasites were obtained antigens used in this study. Furthermore, we used antigens of allergens such as peanut, tomato, strawberry and pollen. To identify shared antigens, proteins were separated by one and two dimensional electrophoresis technique assayed by Western blot using sera of patients with angiostrongyliases. All antigens were recognized by sera from patients infected with angiostrongyliases, being a total of fourteen bands identified as being immunogenic. The fourteen bands were cut out of polyacrylamide gels and analyzed by mass spectrometry. The proteins identified were: Phosphoenolpyruvate carboxykinase, heat shock protein 70 (HSP70), DAPPUDRAFT hypothetical protein, 60 kDa Chaperonin 5, Glyceraldehyde-3-phosphate dehydrogenase, sigma class GST Chain A, Glucose-6-phosphate isomerase, pyruvate dehydrogenase subunit E1, Glutamate dehydrogenase 2, arachin Ahy-1, Full = Allergen Ara h 1, clone P41B, Gly1. The data generated in this study show that there is sharing of antigens between organisms of different taxonomic groups, but also with allergens tested. Moreover, the description and analysis of shared molecular components can help in understanding the evolutionary history and phylogeny of these organisms.